Helmet Detection Device for Motorcycles for Safety Riding Porpuses - Dahlan Abdullah; Badriana Badriana; Misbahul Jannah; Dewi Rahayu; Bambang Setiaji; Cut Ita Erliana (Majlesi Journal of Electrical Engineering)
In today's rapidly advancing technological landscape, the proliferation of motorized vehicles, particularly motorcycles, continues to grow. Motorcycles play a crucial role in facilitating transportation for a broader community. As more daily activities become reliant on road networks, the volume of road users has escalated significantly, resulting in an increased risk of accidents. Unfortunately, many motorcycle riders neglect the importance of wearing helmets, a fundamental safety measure. To address this pressing issue, we propose the development of a helmet detection system for motorcycle riders. This system aims to encourage responsible helmet usage and minimize negligence among motorists. Our research employs an Arduino Uno microcontroller and various components, including the NRF24L01 wireless module, Limit Switch, battery, charger module for input, and Arduino Uno, NRF24L01, and Relay for output. Our study demonstrates that the designed system functions effectively. It operates only when the rider is wearing a helmet, enabling the motorcycle to start by activating a relay that connects power to the motorcycle socket. The Arduino status is triggered when both Limit Switch 1 and 2 are pressed. The maximum distance between the two NRF24L01 modules is found to be 2 meters. Through our experiments, we have successfully demonstrated that the motorcycle can be started only when the rider is wearing a helmet and securely fastens the helmet strap. This innovation promotes driving safety and encourages responsible helmet usage.